ANALISIS IMPLEMENTASI DIVERSI DALAM PENYELESAIAN PERKARA ANAK PELAKU TINDAK PIDANA PENCURIAN (STUDI KASUS PENGADILAN NEGERI LIWA) - Daffa Ladro Kusworo; Rini Fathonah (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
Abstract : The implementation of diversion aims to avoid criminalizing children in the settlement of cases at the Liwa Court. However, the fact is that the number of applications for diversion on the type of crime of theft by children in the last five years only amounted to 6 cases out of 69 cases. The author realizes that indeed not all cases can successfully carry out diversion because there are various obstacles to the facts on the ground, such as the lack of understanding of the community and the victim, as well as judges who handle children's cases. This study uses an empirical juridical research method, which is to approach the Liwa District Court directly in obtaining data on the settlement of diversion efforts in the case of children as perpetrators of the crime of theft at the Liwa District Court. Then the author also applies a descriptive analysis approach to manage qualitative data along with deductive methods in concluding problems. It is hoped that this research can provide a solution to the diversion problem that occurs, and increase the number of diversion processes in the future.